Food Flavor and Price Using the Multiple Linear Regression Method in Predicting Purchase Interest at The Colony Restaurant Hotel Tugu Malang: Flavor Pada Makanan Dan Harga Dengan Metode Regresi Linear Berganda Dalam Prediksi Minat Beli Pada The Colony Restaurant Hotel Tugu Malang - Puspitasari, Reny; Anggraini, Dhita Paramita (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Colony Restaurant is a unique and interesting restaurant located in the city of Malang. Thepurpose of this research is to determine and analyze the influence of flavor in food and price on purchasing interest at The Colony Restaurant Hotel Tugu Malang. This research is explanatory research using quantitative research. The research population consisted of guests visiting the Colony Restaurant Hotel Tugu Malang and the sample size was 100 people. The data collection method used in this research is a questionnaire and the data analysis methods are validity/reliability testing, classical hypothesis testing, multipleregression testing, and hypothesis testing. The results of this research show that the flavorvariable in food has a partially significant influence on purchasing interest at The Colony Restaurant Hotel Tugu Malang, and price has a partially significant influence on purchasinginterest at The Colony Restaurant Hotel Tugu Malang. The results of this research analysisshow that the flavor variables in food and price simultaneously have a significant influenceon purchasing interest at The Colony Restaurant Hotel Tugu Malang